2020
DOI: 10.3233/jrs-194050
|View full text |Cite
|
Sign up to set email alerts
|

Near-miss analysis in a large hospital in southern Brazil: A 5-year retrospective study

Abstract: BACKGROUND: Near-miss analysis is an effective method for preventing serious adverse events, including never events such as wrong-site surgery. OBJECTIVE: To analyze all near-miss incidents reported in a large general hospital in southern Brazil between January 2013 and August 2017. METHOD: We performed a descriptive retrospective study of near-miss incidents recorded in the hospital’s electronic reporting system in a large non-profit hospital (497 beds). The results are expressed as absolute (n) and relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…We excluded another 337 articles after reviewing the full-text citations largely because they neither identified individual NEs nor specified an existing framework (47%), or because they were non-scholarly (eg, media releases; 30%). Thus, our analyses were based on 367 articles 3 4 7–11 18–377. A full list of these articles and the information we extracted from them are found in online supplemental tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded another 337 articles after reviewing the full-text citations largely because they neither identified individual NEs nor specified an existing framework (47%), or because they were non-scholarly (eg, media releases; 30%). Thus, our analyses were based on 367 articles 3 4 7–11 18–377. A full list of these articles and the information we extracted from them are found in online supplemental tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Röhsig et al’s [ 11 ] five-year integrative review on the cost of errors in the medication chain revealed that 94.7% of the authors analyzed the medication prescription stage at some point in their studies and that the average avoidable cost of this type of error corresponds to more than BRL 3 billion/year. Ranchon et al [ 36 ], when studying errors related to cancer patients undergoing chemotherapy treatment, reported that the 436 errors identified could generate 216 additional days of hospitalization and an avoidable cost/year of approximately BRL 624,186.38.…”
Section: Discussionmentioning
confidence: 99%
“…Among all hospital departments, Intensive Care Units (ICUs) are the hospital environment with perhaps the highest volume of prescribed drugs, which favors errors that can compromise patient safety, increase patient length of stay, and, consequently, increase hospital expenses [ 7 , 8 ]. ME prevalence in ICUs varies and has been documented in the literature for a long time [ 3 , 4 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…So-called near misses or almost errors were less frequent in SC than in other units, such as hospitalization, intensive care and pediatrics ( 10 ) . On the other hand, the occurrence of adverse events of very high severity — known as never events — is alarming when it comes to the intraoperative and immediate post-operative period, such as surgery in the wrong laterality, wrong procedure and/or patient, retention of material inside the patient and electrocautery burns ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Los llamados near misses o casi errores ya fueron menos frecuentes en los CQ que en otras unidades, como hospitalización, cuidados intensivos y pediatría ( 10 ) . Por otro lado, resulta alarmante la aparición de eventos adversos de muy alta gravedad – conocidos como never events –, en el intraoperatorio y postoperatorio inmediato, como cirugía en lateralidad incorrecta, procedimiento y/o paciente incorrectos, retención de material en el paciente y quemaduras por electrocauterización ( 11 ) .…”
Section: Introductionunclassified